Continuing cereals research for sustainable health and well-being. Issue 5 (3rd September 2022) - Poole, Nigel; Donovan, Jason; Erenstein, Olaf
ABSTRACT: Cereals research over the past fifty years has led to huge improvements in production, productivity and food security. The current emphasis in agri-nutrition on micronutrients has cast doubt on the need to continue to invest in cereals. However, besides the essential dietary energy content of cereals such as wheat, maize and rice, we argue that there are two important factors to consider. First, the intrinsic micronutrient content of cereals is not often taken into account. As a major dietary component, cereal foods are already an important vehicle for enhanced nutrition, and these characteristics are amenable to further improvement through plant breeding and value chain interventions in processing, manufacturing and distribution. Second, while adverse effects are acknowledged for some people, cereals are a rich source of both dietary fibre and a range of bioactive food components that are also essential for good health and well-being. In particular, the role of the bioactives in combatting non-communicable diseases is becoming more evident. The development community must not assume that the research gains of the last five decades will be sufficient to guarantee future food security. Research into cereals should be implemented as a multi-sectoral and multi-disciplinary activity encompassing whole food systems.